Perception of students with disabilities from CAA/UFPE about remote teaching in the COVID-19 pandemic (Human Factors in Design, 2022)
The advent of the Covid-19 pandemic and the paralysis of face-to-face classes, many universities have adopted emergency remote learning as a way to resume distance activities. Seeking to understand the perception of students regarding this new teaching modality, the present work aimed to identify the main communicational and informational barriers faced by students with disabilities of the Academic Center of Agreste of the Federal University of Pernambuco in remote teaching, detecting the main problems and proposing interventions capable of assisting in the promotion of a more accessible environment regarding the experiences lived by the memos.
Keywords: Accessibility; Universal Design; Assistive Technology; Higher Education; Inclusion